2011
DOI: 10.1002/art.30485
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive role of 129 strain-derivedSle16locus in rheumatoid arthritis in a new mouse model with Fcγ receptor type IIb-deficient C57BL/6 genetic background

Abstract: Objective. Fc␥ receptor type IIb (Fc␥RIIb) is a major negative regulator of B cells, and the lack of Fc␥RIIb expression has been reported to induce systemic lupus erythematosus (SLE) in mice of the C57BL/6 (B6) genetic background. The 129 strainderived Sle16 locus on the telomeric region of chromosome 1 including polymorphic Fcgr2b confers the predisposition to systemic autoimmunity when present on the B6 background. We undertook this study to examine the effect of the Sle16 locus on autoimmune disease in Fc␥R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…These data corroborate the previous findings that polymorphic 129-SLAMs contribute significantly to increased anti-nuclear and/or anti-cytoplasmic autoAbs observed in B6.129.RIIBKO mice [51]. The contribution of FcγRIIB deficiency alone to autoantibody production was previously addressed but conflicting results were reported [20, 23, 24]. We observed a significant effect of FcγRIIB deficiency on a B6 background on AutoAb production.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These data corroborate the previous findings that polymorphic 129-SLAMs contribute significantly to increased anti-nuclear and/or anti-cytoplasmic autoAbs observed in B6.129.RIIBKO mice [51]. The contribution of FcγRIIB deficiency alone to autoantibody production was previously addressed but conflicting results were reported [20, 23, 24]. We observed a significant effect of FcγRIIB deficiency on a B6 background on AutoAb production.…”
Section: Resultssupporting
confidence: 92%
“…These previous studies suggested that lupus-associated SLAM family genes derived from autoimmune-prone mice contribute to autoimmune responses in these strains [8, 22, 23]. Several previous studies have independently described the modest role of FcγRIIB deficiency and the critical role of 129-SLAMs in enhancing overall autoAb production and related lupus pathology [20, 23, 24, 55]. Here, we defined the effects of FcγRIIB deficiency and the predominant role of 129-SLAM locus in the regulation of Spt-GC B cell and GC Tfh responses.…”
Section: Discussionmentioning
confidence: 99%
“…The Fcgr2b −/− mice we independently generated from B6 ES cells ( Fcgr2b B6 −/− ) showed significantly attenuated lupus-like phenotypes (proteinuria and premature mortality) as compared to the backcrossed B6.Fcgr2b 129 −/− (N12) mice (Supplementary Table), consistent with the report of Boross et al (5). This is also consistent with the finding that in addition to FcγRIIB-deficiency, the 129/Sv derived Sle16 locus may be involved in the autoimmune phenotype in B6.Fcgr2b 129 −/− mice based on the analysis of B6.Fcgr2b 129 −/− mice with different lengths of 129/Sv DNA segments around the targeted Fcgr2b gene in a spontaneous arthritis model and an induced tolerance model (37, 38). While these studies supported the conclusion from the early studies that Fcgr2b is an epistatic modifier of autoimmunity, it also demonstrated additional susceptibility factors contributed by 129/Sv genes may have contributed to the severe proteinuria and premature mortality phenotypes observed in B6.Fcgr2b 129 −/− mice (5).…”
Section: Discussionsupporting
confidence: 90%
“…This inhibitory receptor is thought to help maintain tolerance mechanisms that prevent formation of autoantibody-producing B cells and restrain inflammation in response to immune complex deposition (Baerenwaldt et al, 2011; Smith and Clatworthy, 2010). 129-derived gene variants immediately surrounding the deleted Fcgr2b locus in this mouse background are likely to also play a role in the breach in tolerance, consistent with the multigenic nature of lupus (Boross et al, 2011; Harley et al, 2008; Sato-Hayashizaki et al, 2011). …”
Section: Introductionmentioning
confidence: 64%